Clinical characterization of respiratory large droplet production during common airway procedures using high-speed imaging - Müller, Sarina Katrin; Veltrup, Reinhard; Jakubaß, Bernhard; Kniesburges, Stefan; Hübner, Matthias; Kempfle, J. S.; Dittrich, Sven; Dittrich, Sven; Iro, Heinrich; Döllinger, Michael (Scientific Reports, 2021)
During the COVID-19 pandemic, a significant number of healthcare workers have been infected with SARS-CoV-2. However, there remains little knowledge regarding large droplet dissemination during airway management procedures in real life settings. 12 different airway management procedures were investigated during routine clinical care. A high-speed video camera (1000 frames/second) was for imaging. Quantitative droplet characteristics as size, distance traveled, and velocity were computed. Droplets were detected in 8/12 procedures. The droplet trajectories could be divided into two distinctive patterns (type 1/2). Type 1 represented a ballistic trajectory with higher speed large droplets whereas type 2 represented a random trajectory of slower particles that persisted longer in air. The use of tracheal cannula filters reduced the amount of droplets. Respiratory droplet patterns generated during airway management procedures follow two distinctive trajectories based on the influence of aerodynamic forces. Speaking and coughing produce more droplets than non-invasive ventilation therapy confirming these behaviors as exposure risks. Even large droplets may exhibit patterns resembling the fluid dynamics smaller airborne aerosols that follow the airflow convectively and may place the healthcare provider at risk.
CRIS-Team Scopus Importer:2021-06-04

Considerations for Continuing Semielective and Emergency Otolaryngological Procedures During the COVID-19 Pandemic - Müller, Sarina Katrin; Traxdorf, Maximilian; Mantsopoulos, Konstantinos; Gostian, Antoniu Oreste; Sievert, Matti; Koch, Michael; Hübner, Matthias; Iro, Heinrich (Ent-Ear Nose & Throat Journal, 2020)
Introduction: During the COVID-19 pandemic, worldwide over 600,000 human beings died due to the cause of the disease. In order to deescalate the transmission rate and to avoid crush loading the countries medical health systems social distancing, face masks, and lockdowns have been considered essential by the majority of governments. Whereas some countries have highly reduced or completely stopped otorhinolaryngological procedures, other countries have continued selected surgeries. The objective of this study was to analyze procedures and outcomes of continuing semielective and emergency surgeries during the COVID-19 pandemic. Methods: Retrospective analysis of n = 750 patients who received semi-elective or emergency surgery between March 26 and June 16, 2020, in the Otolaryngology Department of the Friedrich-Alexander-University of Erlangen-Nürnberg. All patients were screened for COVID symptoms and swabbed for SARS-CoV-2 prior to surgery. Results: Of the n = 750 patients, n = 699 patients received semielective surgery and n = 51 emergency surgery. For 27 patients, the swab result could not be awaited due to a life-threatening condition. In these cases, surgery was performed in full protective equipment. No patient was tested positive during or after the surgery (follow-up 45 to 127 days). No member of the medical personnel showed symptoms or was tested positive after contact with patients. Due to the continuation of surgeries, patients’ lives were saved and improvement of long-term quality-of-life and outcomes is anticipated. Conclusions: Continuing selected otorhinolaryngological surgeries is crucial for patients’ health, survival, and long-time quality of life, yet, the protection of the medical personnel has to be granted.
CRIS-Team Scopus Importer:2020-09-18
Keywords: COVID-19; false-negative; otorhinolaryngological procedures; patient’s health; SARS-CoV-2 test

COPHYD (Corona Owed Physical Deficiency): The Impact of Lockdown on Cardiopulmonary Function in Paediatric Cardiology Patients - Stabler, Tim; Weigelt, Annika; Rottermann, Kathrin; Wällisch, Wolfgang; Hübner, Matthias; Dittrich, Sven; Schöffl, Isabelle (Klinische Pädiatrie, 2022)
Introduction Due to the Corona-lockdowns the closure of sports facilities and schools has led to a decline in physical activity (PA) for months. PA is essential for maintaining cardiopulmonary function assessed by peak oxygen uptake. Since peak oxygen uptake represents the best predictor for mortality and morbidity in children with congenital heart disease the impact of lockdowns on this parameter is vital. Methods We evaluated retrospectively cardiopulmonary exercise data from our patient collective from before lockdown with twin-paired data from during lockdown. The twin-pairing was achieved by matching patients with similar heart disease, age, sex, and test method. Cardiopulmonary exercise testing was achieved on either the treadmill or the bicycle. Results We were able to twin-pair 90 cases (26 twins with heart disease and 19 healthy twins). There was a significant decrease of cardiopulmonary function (V?O (2) peak: 35.7 +/- 9.8 vs.30.4 +/- 10.6) in the heart disease cohort along with a significant decrease in peak oxygen pulse (13.3 +/- 4.1 vs. 11.4 +/- 4.5), and peak minute ventilation (V ?E: 83.05 +/- 29.08 vs.71,49 +/- 24.96). The healthy children improved over the timeframe, but this only reached significance for peak minute ventilation (81.72 +/- 25.79 vs.97.94 +/- 31.4). Conclusion We observed a significant decline of peak oxygen uptake during lockdown in the group of congenital heart disease (CHD) patients. This involved a loss of cardiac function as well as pulmonary function. This could be explained by limited access to sports facilities and restriction of regular daily movement due to school closure and overprotection. Healthy children improved their pulmonary function. This might be an indication of an improvement of exercise during confinement.
CRIS-Team WoS Importer:2022-10-14

Impact of premature birth on cardiopulmonary function in later life - Weigelt, Annika; Bleck, Steffen; Hübner, Matthias; Rottermann, Kathrin; Wällisch, Wolfgang; Morhart, Patrick; Abu-Tair, Tariq; Dittrich, Sven; Schöffl, Isabelle (European Journal of Pediatrics, 2023)
Pulmonary function is reduced in children after preterm birth. The variety of subgroups ranges from early to late preterm births. Limitations in pulmonary function can be observed even after late preterm birth without signs of bronchopulmonary dysplasia and/or history of mechanical ventilation. Whether this reduction in lung function is reflected in the cardiopulmonary capacity of these children is unclear. This study aims to investigate the impact of moderate to late premature birth on cardiopulmonary function. Cardiopulmonary exercise testing on a treadmill was performed by 33 former preterm infants between 8 and 10 years of age who were born between 32 + 0 and 36 + 6 weeks of gestation and compared with a control group of 19 children born in term of comparable age and sex. The former preterm children achieved comparable results to the term-born controls with respect to most of the cardiopulmonary exercise parameters (V˙O2peak43.9±6.6mlkgminminvs.41.9±8.8mlkg/min) . The only differences were in a slightly higher oxygen uptake efficiency slope (OUESof1.6±0.4vs1.4±0.4) and higher peak minute ventilation V˙Epeakof55.2±11.3ml/minvs.49.1ml±8.8/min) in the group of children born preterm. With respect to heart rate recovery (-35.3±13.8bpmvs.-37.2bpm±14.0after1min) and breathing efficiency (V˙E/V˙CO2of35.9±4.1vs34.0±4.6) , there were no significant differences. Conclusion: Children born preterm did not show limitations in cardiopulmonary function in comparison with matched controls. What is Known: • Preterm birth is associated with reduced pulmonary function in later life, this is also true for former late preterms. • As a consequence of being born premature, the lungs have not finished their important embryological development. Cardiopulmonary fitness is an important parameter for overall mortality and morbidity in children and adults and a good pulmonary function is therefore paramount. What is New: • Children born prematurely were comparable to an age- and sex-matched control group with regards to almost all cardiopulmonary exercise variables. • A significantly higher OUES, a surrogate parameter for VO 2 peak was found for the group of former preterm children, most likely reflecting on more physical exercise in this group. Importantly, there were no signs of impaired cardiopulmonary function in the group of former preterm children.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Cardiopulmonary exercise testing; Habitual exercise; Premature birth; Sports

Juvenile Larynxpapillomatose: Therapieoptionen und Literaturübersicht - Hübner, Matthias; Schützenberger, Anne; Traxdorf, Maximilian; Dittrich, Sven; Iro, Heinrich; Müller, Sarina Katrin (Monatsschrift Kinderheilkunde, 2022)
Background: Despite various therapeutic options, there is currently no cure for juvenile onset recurrent respiratory laryngeal papillomatosis (JORRP). Additionally, for the majority of these therapeutic options mild to severe side effects have been described. Objective: Analysis of the effects and side effects of previous and current therapeutic options. Discussion of active ingredients, dosage and administrative form of the available drugs. Material and methods: Review of literature and analysis of the therapeutic options concerning effects and side effects, active ingredients, dosage and administrative form. Results: Surgery remains the gold standard of all treatment options. There are multiple therapeutic options in the literature; however, no treatment options currently lead to a complete remission. Maintaining the function, increasing the time interval between interventions and diminishing the papilloma load in cases of recurrence remain the utmost priority. Conclusion: There are several promising therapeutic options for the treatment of JORRP; however, the current data situation is not sufficient for a general recommendation or guidelines. In the future, further prospective studies with a larger patient population/juvenile population are necessary.
CRIS-Team Scopus Importer:2022-09-20
Keywords: Bevacizumab; Human papillomavirus; Laryngeal papillomatosis; Programmed cell death 1 receptor; Vaccine

Management von Patienten mit Tracheostoma während der COVID-19-Pandemie: Literaturüberblick und Demonstration - Kempfle, J. S.; Löwenheim, H.; Hübner, Matthias; Iro, Heinrich; Müller, Sarina Katrin (HNO, 2020)
Background: Since emergence of the new coronavirus in China in December 2019, many countries have been struggling to control skyrocketing numbers of infections, including among healthcare personnel. It has now been clearly demonstrated that SARS-CoV‑2 resides in the upper airways and transmits easily via aerosols and droplets, which significantly increases the risk of infection when performing upper airway procedures. Ventilated COVID-19 patients in a critical condition in the intensive care unit may require tracheotomy for long-term ventilation and to improve weaning. However, the risk of secondary infection of medical personnel performing subsequent tracheostomy care remains unclear. Objective: This study aimed to evaluate the risk of droplet dispersion during tracheostomy tube change and overview tracheostomy tube change in COVID-19 patients. Materials and methods: The current literature was reviewed, quantitative and qualitative analyses of droplet formation during tracheostomy tube change in n = 8 patients were performed, and an overview of and checklist for tracheostomy tube change were compiled. Results: This study demonstrates that tracheostomy tube change, in particular insertion of the new tube, may cause significant droplet formation. The aerosolization of particles smaller than 5 µm was not analyzed. Conclusion: Our data, together with the current literature, clearly emphasize that tracheostomy care is associated with a high infection risk and should only be performed by a small group of well-trained, maximally protected healthcare personnel.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Aerosols; COVID-19; Droplets; PPE; Tracheostomy tube change

Sports despite masks: no negative effects of FFP2 face masks on cardiopulmonary exercise capacity in children - Weigelt, Annika; Schöffl, Isabelle; Rottermann, Kathrin; Wällisch, Wolfgang; Müller, Susanna; Dittrich, Sven; Hübner, Matthias (European Journal of Pediatrics, 2023)
Face masks were recognized as one of the most effective ways to prevent the spread of the COVID-19 virus in adults. These benefits were extended to children and adolescents. However, the fear of negative consequences from wearing a face mask during physical exercise led to cancellations of physical education lessons. This further decreased the amount of physical activity available to children and adolescents during the pandemic. However, there is little published data on the potential adverse effects of wearing the most effective and partially mandatory FFP2/N95 face masks during PE or physical activity (PA) in this age. Even though the pandemic has been declared as passed by the WHO, the rise of a new pandemic and thus the use of face masks for limiting its spread is inevitable, so we need to be better prepared for alternative options to lockdown and limitation of PA in such a scenario. Twenty healthy children aged 8–10 years performed two identical cardiopulmonary exercise tests as an incremental step test on a treadmill within an interval of 2 weeks, one time without wearing a protective mask and one time wearing an FFP2 mask. The cardiopulmonary exercise parameter and especially the end-expiratory gas exchange for oxygen and carbon dioxide (petO2 and petCO2) were documented for each step, at rest and 1 min after reaching physical exhaustion. Twelve boys (mean age 8.5 ± 1.4 years) and 8 girls (mean age 8.8 ± 1.4 years) showed no adverse events until maximal exertion. The mean parameters measured at peak exercise did not differ significantly between both examinations (mean peak VO2 = 42.7 ± 9.5 vs 47.8 ± 12.9 ml/min/kg, p = 0.097, mean O2pulse 7.84 ± 1.9 ml/min vs. 6.89 ± 1.8, p = 0.064, mean VE/VCO2slope 33.4 ± 5.9 vs. 34.0 ± 5.3, p = 0.689). The only significant difference was the respiratory exchange rate (RER, 1.01 ± 0.08 vs 0.95 ± 0.08, p = 0.004). The measured respiratory gases (end-tidal O2 and CO2) decreased and respectively increased significantly in almost every step when wearing an FFP2 mask. However, these levels were well below hypercapnia and above hypoxia. Conclusion: In this study, no significant differences in the cardiorespiratory function at peak exercise could be discerned when wearing an FFP2/N95 face mask. While the end-tidal values for CO2 increased significantly and the end-tidal values for O2 decreased significantly, these values did never reach levels of hypercapnia or hypoxia. Furthermore, the children terminated the exercise at a lower RER and heart rate (HR) suggesting a subconscious awareness of the higher strain. Since the detrimental effects of limiting sports during the pandemic are well documented, stopping PE lessons altogether because of the minor physiological effects of wearing these masks instead of simply stopping pushing children to perform at their best seems premature and should be reconsidered in the future. What is Known: • Wearing a face mask has an influence on psychological, social, and physiological functions in adults. • Because of the observed effects of wearing face masks in adults, physical activity in children was limited during the pandemic. What is New: • Wearing an FFP2/N95 mask during physical activity did not lead to hypercapnia or hypoxia in children in this study. • Even though end-tidal CO2 values were significantly higher and end-tidal O2 values significantly lower when wearing an FFP2/N95 face mask, no pathological values were reached.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Coronavirus; COVID-19; End-tidal CO; End-tidal O; Oxygen saturation; Treadmill testing; VO